2017
DOI: 10.1038/cddis.2016.457
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 overexpression in human cholangiocarcinoma and promotion of cell growth via apoptosis inhibition

Abstract: Histone deacetylase 3 (HDAC3) has an oncogenic role in apoptosis and contributes to the proliferation of cancer cells. MI192 is a novel HDAC3-specific inhibitor that displays antitumor activity in many cancer cell lines. However, the role of HDAC3 and the antitumor activity of its inhibitor MI192 are not known in cholangiocarcinoma (CCA). The present study aims to identify the target of MI192 in CCA as well as evaluate its therapeutic efficacy. CCK8 and colony formation assays showed that HDAC3 overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
1
36
1
Order By: Relevance
“…Since metabolic reprogramming in tumor cells could possibly endow the cells with resistance to chemotherapies (30,31), we thought that low concentrations of metformin could alter the metabolic abnormalities of tumor cells, causing the cells to become fragile and sensitive to chemotherapy. Our previous data showed that HDAC3 is a potential chemotherapeutic target (20). However, the present study found that the new selective HDAC3 inhibitor, BG45, could hardly induce CCA cellular apoptosis.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Since metabolic reprogramming in tumor cells could possibly endow the cells with resistance to chemotherapies (30,31), we thought that low concentrations of metformin could alter the metabolic abnormalities of tumor cells, causing the cells to become fragile and sensitive to chemotherapy. Our previous data showed that HDAC3 is a potential chemotherapeutic target (20). However, the present study found that the new selective HDAC3 inhibitor, BG45, could hardly induce CCA cellular apoptosis.…”
Section: Discussioncontrasting
confidence: 64%
“…HuCCT1 and RBE cells were transfected using Lipofectamine RNAiMax reagent (Invitrogen; Thermo Fisher Scientific, Inc.), following the manufacturer's protocol. HDAC3 siRNA was produced as described previously (20). Briefly, 50 pmol siRNA and 0.5 ml Opti-MEM I Medium (Invitrogen; Thermo Fisher Scientific, Inc.) were mixed, and then 5.5 µl RNAiMax reagent was added to each well of a 6-well plate and incubated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite recent improvements in cholangiocarcinoma treatment, surgical resection and transplantation is still the main therapy, as this can cure early-staged patients [5,6]. Unfortunately, there are no specific biomarkers or unique clinical manifestations for cholangiocarcinoma, meanwhile, HC is typically characterized by advanced stage diagnosis.…”
Section: Introductionmentioning
confidence: 99%